2016
DOI: 10.1016/j.vetpar.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors and prevalence of haemoplasma infection in dogs

Abstract: Mycoplasma haemocanis (Mhc) and 'Candidatus Mycoplasma haematoparvum' (CMhp) are canine haemoplasma species that can induce anaemia in immunocompromised and/or splenectomised dogs. This study aimed to determine the prevalence and phylogeny of canine haemoplasma species in dogs from Nigeria and describe any risk factors for infection. Canine haemoplasma species-specific and generic haemoplasma qPCR assays were used. The species-specific qPCR assays found Mhc infection in 18 of 245 dogs (7.3%), and CMhp infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
2
10
2
Order By: Relevance
“…In the present study Mhc has higher molecular prevalence than CMhp and this result is in accordance with previous publications [5,9] . Three dogs (1.76%) were found to be infected for both Mhc and CMhp.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study Mhc has higher molecular prevalence than CMhp and this result is in accordance with previous publications [5,9] . Three dogs (1.76%) were found to be infected for both Mhc and CMhp.…”
Section: Discussionsupporting
confidence: 94%
“…Mhc, CMhp and Mhc + CMhp prevalences were 2.94% (CI 1.06-6.22), 0.59% (CI 0.03-2.57) and 1.76% (CI 0.44-4.52) respectively with this study. Low prevalence of hemoplasmas determined with this study was similar to data from Italy 4.5% [10] and Nigeria with 7.7% [5] . While higher prevalences were reported in Portugal 40% [2] , Iran 23% [9] and Turkey 15.3% [4] ; low prevalence was from USA 1.3% [3] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…No dog had a history of splenectomy. In a previous study, Aquino et al (2016) did not identify any significant age or breed predisposition despite detecting M. haemocanis infection more in males (differing from that observed in this study).…”
Section: Introductioncontrasting
confidence: 99%
“…However, the infection rate in this study was higher than the observed prevalence of M. haemocanis (1.9%) and Candidatus M. haematoparvum (0.6%) in 154 dogs from Ribeirão Preto (ALVES et al, 2014). The difference between the prevalences may vary according to the population sampled, the distribution of R. sanguineus (a probable vector), or the sensitivity of the diagnostic technique employed (AQUINO et al, 2016). Table 1 shows factors investigated for association with M. haemocanis infection.…”
Section: Introductionmentioning
confidence: 51%